PROMOTING BIODIVERSITY CONSERVATION WITH SUPRA-REGIONAL CONNECTIONS. CASE STUDY OF A MEDITERRANEAN REGION, TUNISIA - Boussema, Safa Bel Fekih; Cohen, Marianne; Khebour Allouche, Faiza (International Journal of Research -GRANTHAALAYAH, 2022)
Ecological network aims to ensure the survival of animal and plant species. It is considered a new public policy to avoid the loss of biodiversity by persevering the landscape connectivity and natural habitats from fragmentation. This research proposes a methodology that is based on identifying the sub-frames representatives of the study area and their selected species. Thus, the methodology developed comprises five steps. In the first step, the land use map was analyzed. Then, the major types of habitat were extracted. In the third step, a forest habitats sub-frame, a semi-open habitats sub-frame, and a wetlands sub-frame were determined. Then, the selected species were characterized. Finally, supra-regional connections were proposed to enhance biodiversity conservation in this region. As a result, crucial ecological corridors can be optimized along with the proposed supra-regional connections to the neighboring cities, and contributing to promote sustainable projects. Thus, the methodological approach developed can be a reference to other local or regional studies. It can be integrated into planning documents that should be a part of a decision-making perspective in public policies for sustainable landscapes, preserving biodiversity, and enhancing well-being.